Histopathological study of neoplastic lesions of large intestine in Kashmir Valley, India - Rasool, Mohsin-ul; Mubeen, Basharat; Andrabi, Riyaz-u-Saif; Hamid, Sajad; Rasool, Zubaida; Shah, Parveen; Shah, Omer Javid (International Journal of Research in Medical Sciences, 2017)
Background: Aim of current study was to study the histopathological spectrum of neoplastic lesions of large intestine and histopathological pattern of colorectal carcinoma in young adults. Methods:We took a combined retrospective & prospective study in the department of pathology. The specimens were collected from subjects diagnosed as colorectal carcinomas in histopathology department and clinical details were sought from the medical records. Variables like age, sex, dietary habit, relevant history, tumor size, location, type of lesion, histological pattern of patients were checked. Results:In the series of 446 patients of colorectal neoplasm, maximum number of patients presented in 4th to 6th decade of life (47.30%), while as (15.46%) were between 20-40 years. The youngest patient with an adenocarcinoma was 18 years (male) of age and the oldest one was 80 years (male) of age. Average age of patients was 50.50 years. The male to female ratio was 1.3:1. The study revealed that the carcinoma of ascending colon was much more prevalent, constituting 107 (40.07%) cases. The proportion of well differentiated carcinoma was highest in left side colon and rectum. The incidence of moderately differentiated and poorly differentiated carcinoma was greater on right side colon. Conclusion:Adenocarcinoma is the most common histological variant of colon carcinomas.